Two Phenomena in English Loanword Adaptation in Swedish - Antunović, Goranka (Array, 1997)
Anglicisms in Swedish share many common characteristics of anglicisms, and loanwords in general, in other European languages. However, in their adaptation one can note some interesting and peculiar phenomena that are either missing or are much less prominent in other languages. The article discusse two of them: a) a pronounced orthographic trend, namely preservation of the English spelling within the Swedish system. Two thirds of the anglicisms in the 1461-item corpus compiled by the author are spelled in the same way as their English models ; b) plural suffix -s, repeatedly borrowed into Swedish. Several factors promote its usage so that it appears as the only possibility or as one of the alternatives in the plural of more than 15% of substantives in the corpus, i.e. more commonly than some "proper" Swedish suffixes.